2008
DOI: 10.1016/j.neuint.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

TNF is a key mediator of septic encephalopathy acting through its receptor, TNF receptor-1

Abstract: In this study, we demonstrate that mice deficient in TNFR1 (TNFR1 -/-) were resistant to LPSinduced encephalopathy. Systemic administration of lipopolysaccharide (LPS) induces a widespread inflammatory response similar to that observed in sepsis. Following LPS administration TNFR1 -/-mice had less caspase-dependent apoptosis in brain cells and fewer neutrophils infiltrating the brain (p<0.039), compared to control C57Bl6 (TNFR1 +/+ ) mice. TNFR1-dependent increase in aquaporin (AQP)-4 mRNA and protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(162 citation statements)
references
References 55 publications
7
141
0
6
Order By: Relevance
“…Also, they reported that interleukin 6 levels in brain tissue are not significantly changed after 24 h. In the literature, TNF-alpha was commonly measured as a marker for sepsis associated encephalopathy in the brain tissue. The interleukin 6 levels were measured in serum [1,19,2124]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they reported that interleukin 6 levels in brain tissue are not significantly changed after 24 h. In the literature, TNF-alpha was commonly measured as a marker for sepsis associated encephalopathy in the brain tissue. The interleukin 6 levels were measured in serum [1,19,2124]. …”
Section: Discussionmentioning
confidence: 99%
“…TNF-α increases neuronal apoptosis and brain edema by stimulating neutrophil infiltration in the brain tissue. It has been shown that TNF-α is related to aquaporin 4 receptor up-regulation and cerebral edema, and has a key role in SAE [21]. Long-term memory deficit and neuronal loss was seen in experimental models, similar to signs in patients with sepsis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we recently reported evidence of a similar vicious cycle during acute inspiratory hypoxia in healthy humans (Bailey et al, 2009). In the healthy state, iNOS activation is low, but this enzyme may be induced in glial cells and increase NO production in response to a variety of noxious stimuli (Pacher et al, 2007), such as TNF-a and IL-1b (Wong et al, 1996;Alexander et al, 2008) and, possibly, decreased ambient NO levels (Galijasevic et al, 2003). A decreased NO bioavailability may therefore act in concert with focal inflammation to enhance iNOS expression.…”
Section: No Depletionmentioning
confidence: 99%
“…In an animal model, these authors demonstrated that endotoxemia-triggered infl ammation in the brain led to an alteration in the blood-brain barrier, including an upregulation of aquaporin 4 and associated brain edema. Th is sequence of events appeared to be mediated by TNF-α signaling through the TNF receptor 1 [14].…”
Section: Eff Ects Of Sepsis On the Blood-brain Barrier And The Vasculmentioning
confidence: 99%
“…In an animal model, these authors demonstrated that endotoxemia-triggered infl ammation in the brain led to an alteration in the blood-brain barrier, including an upregulation of aquaporin 4 and associated brain edema. Th is sequence of events appeared to be mediated by TNF-α signaling through the TNF receptor 1 [14].In a recent magnetic resonance imaging (MRI) study in nine humans with septic shock and brain dysfunction, sepsis-induced lesions could be documented in the white matter suggesting blood-brain barrier breakdown [15]. However, in a pathologic study no evidence of cerebral edema was reported in 23 patients who died of septic shock [4].…”
mentioning
confidence: 99%